Media Environment as Factor of Realization of Creative Potential of Future Teachers` in the Mountain Schools of the Ukrainian Carpathians - Lebedieva, Alla (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article shows up “media environment” as a factor of future teachers` creative potential realization in the mountainous schools of the Ukrainian Carpathians. The problem of using media environment as a factor of future teachers` creative potential in the mountainous schools of the Ukrainian Carpathians and the ways of its optimization is the main point of this research. Highlights ways to modernize social and professional orientation training of students in the creative process of nature is situates in information education and educational environment of high school. We consider the causal link use media environment as a factor of future teachers` creative potential and complexity of the teacher in the mountainous schools of the Ukrainian Carpathians. The basic function of the media environment are extensity, instrumental, communicative, interactive, multimedia. Reveals some aspects of training students to creatively active teaching process we describe subjects with objective possibilities in the formation of professional skills of future teachers` and which directly affect the realization of creative potential – “Ukrainian folk art”, “Basic recitation and rhetoric”, “The basis of pedagogical creativity”. The necessity of creating a full-fledged media environment in higher education is important condition of successful education as an important factor that allows the efficiency of the creative potential of future teachers` in the mountainous schools of the Ukrainian Carpathians.